Contained myocardial rupture: a variant linking complete and incomplete rupture. Issue 2 (18th January 2005) - Helmy, T A; Nicholson, W J; Lick, S; Uretsky, B F
Abstract : Myocardial rupture is an uncommon complication of myocardial infarction, often with devastating haemodynamic consequences. Although rupture is usually fatal, when patients do survive, the majority present with a pseudoaneurysm in which the rupture is sealed by a haematoma on the epicardial surface of the heart. Cases in which all myocardial layers are dissected except the epicardium or visceral pericardium have been included under this subheading. The authors describe such a case and suggest the pathological description of a "contained myocardial rupture". This link between complete and incomplete myocardial rupture may allow a more conservative management approach to be pursued.